Pedagogical Aspects of Forming Sports Motivation - Khatamov Zafarjon Nazirjonovich (European Science Publishing, 2023)
On the basis of the theoretical analysis of scientific and methodical literature, the nature and content of sports motivation and its correlation with personal characteristics of athletes were determined. Pedagogical conditions for the formation of sports motivation of volleyball players aged 9-13 were determined.
Keywords: motive, sports motivation, sports activity, personal characteristics, level of demands.